Effect of Geometric Imperfection on the Dynamic of Elevated Water Tanks - Nasser Dine Hadj-Djelloul; M. Djermane (Salehan Institute of Higher Education, 2020)
The elevated tanks are considered as very sensitive structures in seismic movement condition. Moreover, the conical steel tank manufacturing without local geometric imperfection seems to be too difficult. In generally, the latter is the most responsible factor to define the shell structures buckling capacity. For this reason, several theoretical and experimental researchers studied the performance of this type of structure under seismic loading. The present study aims to demonstrate the local geometric imperfection effect on dynamic buckling of elevated water tank. Using the three dimensions finite element technique to study the seismic response of perfect and imperfect elevated water tank was established taking into account the following factors; the interaction fluid structure (FSI), the wall flexibility, the local geometric imperfection, the nonlinear time history analysis, the material and geometric nonlinearity, and this by the application of three different instability criteria for the critical PGA estimate. The critical PGA of the imperfect elevated water tank numerical models decreased by 45, 45% compared to the elevated water tank numerical model without local geometric imperfection. The obtained results confirm the local geometric imperfection effect on dynamic buckling of elevated water tanks.